Respostas
respondido por:
0
2,5(2-y)=30y+30
5 - 2,5y = 30y + 30
5- 2,5y - 30y = 30
- 32,5y = 30 - 5
- 32,5y= 25
25
y = --------------
- 32,5
25
y = - ----------- ( divide AMBOS por 5)
32,5
5
y = - --------
6,5
1,2(x-4)=1,2+2,4
1,2x - 4,8 = 3,6
1,2x = 3,6 + 4,8
1,2x = 8,4
8,4
x = -----------
1,2
x= 7
5 - 2,5y = 30y + 30
5- 2,5y - 30y = 30
- 32,5y = 30 - 5
- 32,5y= 25
25
y = --------------
- 32,5
25
y = - ----------- ( divide AMBOS por 5)
32,5
5
y = - --------
6,5
1,2(x-4)=1,2+2,4
1,2x - 4,8 = 3,6
1,2x = 3,6 + 4,8
1,2x = 8,4
8,4
x = -----------
1,2
x= 7
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás